Pengaruh Kemudahan dan Manfaat Mobile Banking Terhadap Kepuasan Mahasiswa Jurusan Perbankan Syari’ah UIN Sumatera Utara - Jelita Handayani Rambe; Kiki Andrea Putri Hasibuan (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
Mobile banking services provided by Islamic banks offer various conveniences to satisfy some people with ease of transaction. This study aims to determine partially and simultaneously the convenience and benefits of mobile banking and the influence of the most dominant variables on student satisfaction studying Islamic banking at UIN North Sumatra. This research uses quantitative techniques and literature study. The survey sample consisted of 100 respondents who were undergraduate students at UIN North Sumatra and undergraduate students in Islamic banking who used mobile banking. This data collection model uses a survey. The results showed that (a) the